2021
DOI: 10.1371/journal.pone.0255729
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in utilizing lipid-lowering agents in non-institutionalized population in the U.S.: Application of a theoretical framework

Abstract: Cardiovascular diseases are a major cause of death globally. Epidemiological evidence has linked elevated levels of blood cholesterol with the risk of coronary heart disease. However, lipid-lowering agents, despite their importance for primary prevention, are significantly underused in the United States. The objective of this study was to explore associations among socioeconomic factors and the use of antihyperlipidemic agents in 2018 in U.S. patients with hyperlipidemia by applying a theoretical framework. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…31 Eliminating observed health disparities will require a multisectoral approach: community engagement for healthy lifestyle interventions, such as access to affordable healthy food options and safe neighborhoods that promote increased physical activity; government-level policies to address systemic racism and health inequities; and efforts to provide equitable access to medical care, including removing structural barriers and reluctance to seek medical care. [32][33][34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…31 Eliminating observed health disparities will require a multisectoral approach: community engagement for healthy lifestyle interventions, such as access to affordable healthy food options and safe neighborhoods that promote increased physical activity; government-level policies to address systemic racism and health inequities; and efforts to provide equitable access to medical care, including removing structural barriers and reluctance to seek medical care. [32][33][34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidaemia is very often involved in dyslipidaemia, which have abnormalities in one or more parameter of the biochemical lipid triad [1] . It has previously been shown that excess intake of HFD can be at increased risk for abnormal lipid homeostasis [2] .…”
Section: Introductionmentioning
confidence: 99%